2011
DOI: 10.1128/jvi.01666-10
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Domains on the Fusion (F) Protein Trimer That Influence the Hemagglutinin-Neuraminidase Specificity of the F Protein in Mediating Cell-Cell Fusion

Abstract: For most paramyxoviruses, virus type-specific interaction between fusion (F) protein and attachment protein (hemagglutinin-neuraminidase [HN], hemagglutinin [H], or glycoprotein [G]) is a prerequisite for mediating virus-cell fusion and cell-cell fusion. Our previous cell-cell fusion assay using the chimeric F proteins of human parainfluenza virus 2 (HPIV2) and simian virus 41 (SV41) suggested that the middle region of the HPIV2 F protein contains the site(s) that determines its specificity for the HPIV2 HN pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 38 publications
2
25
1
Order By: Relevance
“…It is important in this context to note that the HN protein specificity of the F protein also is not solely defined by the primary structure of the F head domain, as we have reported previously (21,31).…”
Section: Discussionmentioning
confidence: 99%
“…It is important in this context to note that the HN protein specificity of the F protein also is not solely defined by the primary structure of the F head domain, as we have reported previously (21,31).…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, the HN specificity domains were further localized into two smaller regions, called M1 (amino acids from 234 to 246) and M2 (amino acids from 278 to 285) (48). Of note, these HN specificity domains were located in the surface of the F trimer based on the predicted structure (48). A similar region in the F protein of canine distemper virus (CDV) mediates the interaction with the homologous H protein (28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using chimeric F proteins derived from hPIV2 and simian virus 41 (SV41) have shown that a region composed of 144 amino acids (from positions 227 to 370) in HPIV2 F protein harbors the site(s) that determines the specificity of the interaction with homologous HN protein (47). Most recently, the HN specificity domains were further localized into two smaller regions, called M1 (amino acids from 234 to 246) and M2 (amino acids from 278 to 285) (48). Of note, these HN specificity domains were located in the surface of the F trimer based on the predicted structure (48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our previous chimeric analyses of the F proteins of two closely related rubulaviruses, human parainfluenza virus 2 (HPIV2) and simian virus 41 (SV41), suggested that a 144-amino-acid region (designated the middle region) in the ectodomain of the HPIV2 F protein contains the site(s) that determines its specificity for the HPIV2 HN protein in the induction of cell-cell fusion (22). Recently, we found that replacement of two domains in the head region of the PIV5 F protein with the SV41 F counterparts bestowed on the PIV5 F protein the ability to induce cell-cell fusion on coexpression with the SV41 HN protein without significantly affecting its ability to induce fusion with the PIV5 HN protein (23). Similarly, mutations of four amino acids in the head region of the F protein of canine distemper virus (CDV) strain Onderstepoort impair the ability to induce cell-cell fusion with the co-expressed measles virus (MV) hemagglutinin (H) protein without significantly affecting the ability to induce fusion with the CDV H protein (24).…”
mentioning
confidence: 99%